2011
DOI: 10.1007/s00423-011-0800-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric leakage after sleeve gastrectomy—clinical presentation and therapeutic options

Abstract: The location of leakage, and the presence or absence of an intraabdominal drain are determining factors for its treatment. UGI radiography with contrast media and gastroscopy are comparable and superior to standard CT scan. Stent graft application is a promising therapy in case of proximal leakage; re-suture or resection of the staple line are possible solutions in case of a distal leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 30 publications
0
44
0
5
Order By: Relevance
“…According to the time of onset, Csendes et al [6] classified leakage as early when appearing within the first four postoperative days, intermediate when appearing in postoperative days [5][6][7][8][9] and late when occurring in or after the tenth postoperative day. By clinical presentation and extent of dissemination, type I or subclinical leakage was defined as well localized leak without dissemination into the pleural or abdominal cavity and without systemic clinical manifestations, and usually they are easy to treat medically.…”
Section: Leak Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the time of onset, Csendes et al [6] classified leakage as early when appearing within the first four postoperative days, intermediate when appearing in postoperative days [5][6][7][8][9] and late when occurring in or after the tenth postoperative day. By clinical presentation and extent of dissemination, type I or subclinical leakage was defined as well localized leak without dissemination into the pleural or abdominal cavity and without systemic clinical manifestations, and usually they are easy to treat medically.…”
Section: Leak Classificationmentioning
confidence: 99%
“…It can also be an effluent of gastrointestinal contents through a suture line, which may collect near the anastomosis, or exit through the wall or the drain [4]. Leak is the second most common cause of death after bariatric surgery with an overall reported mortality rate of 0.4 % [5]. The aim here is to overview the current pathogenic and favoring factors of leakage after LSG on the basis of recent literature evidence and to summarize the suitable evidences and preventive measures according to the Oxford centre for evidence-based medicine (2011) evidence levels (EL).…”
Section: Introductionmentioning
confidence: 99%
“…Following the development of a fistula, the tissue surrounding the fistula orifice is friable and edematous due to inflammation with consequent ineffectiveness of surgical sutures at that location to close the fistula orifice [3,9], ultimately requiring total gastrectomy in some patients [4]. As these patients are often seriously ill with sepsis, a second major surgery often results in severe stress with a consequent higher risk of mortality [14].…”
Section: Discussionmentioning
confidence: 99%
“…The management of these fistulas is usually difficult and results in prolonged hospitalization. In the past, patients were re-operated with surgical attempts at closing the fistulas often ending in failure and total gastrectomy [2,9]. Several studies have shown the importance and efficacy of an endoscopic approach which is minimally invasive for the management of these complications, thus avoiding the risks of surgical re-intervention [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Some authors recommend upper gastrointestinal radiography and endoscopy instead of CT suggesting on the fact that obesity produces technical difficulties and low image quality. [21] Early postoperative leak tests with methylene blue and gastrografin are recommended by many authors although they are shown neither specific nor sensitive by restrospective reviews. [22,23] It is crucial to recognize the fact that a normal test cannot rule out a fistula and may cause delay in diagnosis.…”
Section: Introductionmentioning
confidence: 99%